Euphorbia prostrata Aiton (subgen. Chamaesyce): a new alien species in the Tunisian flora - El Mokni, Ridha (Biodiversity: Research and Conservation, 2025)
Euphorbia prostrata Aiton (Euphorbiaceae), native to tropical and subtropical regions of the Americas, is also scattered as an alien/naturalized species in various parts of the Old World, including several Mediterranean and African countries. This paper documents for the first time its several localities in Tunisia. It presents a morphological description with photographs, ecological features, a first map of distribution and taxonomic notes, concerning comparisons with closely related species. In addition, an updated key to identification of annual Euphorbia species of subgen. Chamaesyce sect. Anisophyllum in Tunisia is proposed.